Efektivitas Konseling Rational Emotive Behavior Therapy (REBT) dengan Teknik Cognitive Disputing dalam Meminimalisir Perilaku Agresif Peserta Didik dari Keluarga Broken Home - Syavira; Kasih, Fitria; Wira Nita, Rahma (Kartika: Jurnal Studi Keislaman, 2025)
This research is motivated by the phenomenon aggressive behavior in students from broken homes, which can interfere with their social and emotional development. The study aims to describe aggressive behavior before and after Rational Emotive Behavior Therapy (REBT) counseling with cognitive disputing techniques, as well as test its effectiveness in reducing aggressive behavior. The research used an experimental method with a One Group Pretest-Posttest design. Samples were determined through purposive sampling techniques with a population of 14 people and a sample of 2 people, instruments in the form of questionnaires, and data analysis was carried out with percentage intervals and t- tests. The results showed that before counseling, aggressive behavior of students was in the high category, while after counseling with cognitive disputing techniques, aggressive behavior was in the low category. The results of the t-test showed a significant difference between before and after the intervention, proving the effectiveness of REBT counseling. This study recommends BK teachers to apply REBT counseling with cognitive disputing techniques as a strategy to reduce the aggressive behavior of broken home students at SMK Negeri 2 Bukittinggi.